A Perspective on the Photofading of Organic Colorants - Anthony Harriman (Colorants)
This perspective presents an account of the underlying features associated with the photofading of organic colorants. Photofading is commonly known to the scientific community as photodegradation or photooxidation, while in earlier times the more grandiose term “light fastness” was commonplace. This is a subject of immense diversity and significance, but there are many challenges to be faced when attempting mechanistic reasoning. The text is illustrated by descriptions of several systems taken from the scientific literature, together with anecdotes related to the principal researchers. The chemical challenges to be overcome in order to design photostable materials are outlined and reference is made to the natural world. It is stressed that the journal Colorants would welcome submissions in this field.